Questioning the Criminal Threat Formulation Policy on Electoral Crime - Waluyadi, Waluyadi (Jurnal Legisci, 2024)
Law Number 10 of 2016 should be formulated differently from other laws, as it pertains to the second amendment to Undan-Law Number 1 of 2015, which stipulates government regulations instead of Law Number 1 of 2014, which deals with the election of governors, regents, and mayors into Law. The enactment of the Law coincides with the conduct of elections, which is not less significant, and the Law's unique nature makes it so that regional head election activities are essentially administrative. The Law is enacted every five (five) years. It is essential to take these specifics into account when forming. Both at the time of application and execution, poorly formulated policies will have consequences. Furthermore, the issue that this tulip will highlight is how the Law's policy was formulated, particularly regarding the inclusion of criminal threats for those who commit electoral offenses. This study uses a normative methodology. It is a qualitative kind of study. Secondary data is what is utilized. Researching the literature is how data is gathered. Presenting the facts in a descriptive format, the analysis is prescriptive. As per the study's findings, electoral crimes are defined as administrative infractions or crimes against election provisions. The legal penalties for electoral crimes consist of imprisonment and fines, with no enforcement measures. Election crime resolution is comparatively quick and applies across Indonesia without considering the specific circumstances in each area.